Determination of free phenolics and combined phenolics in foliage of Magnolia sieboldii K. Koch - Gao Hongbing; Wang Huan; Du Fengguo (Functional Materials, 2016)
In order to further understand the type and content of phenolics of Magnolia sieboldii K. Koch, the method of high performance liquid chromatography (HPLC) was used for measuring qualitatively and quantitatively free phenolics, combined phenolics and ester phenolics in foliage. Chromatographic conditions: C18 column, Mobile phase A pump 0.5% formic acid aqueous solution, B pump is 0.5% Formic acid methanol solution, The total flow rate of 0.8 ml/min, the column temperature 30C, SPD detector. The experimental results showed that the foliage contained coumaric acid and chlorogenic acid of two kinds of free phenolics, caffeic acid, coumaric acid and catechin coumarin in combined state, coumarin and coumaric acid in ester form, content range was 0.012 ~ 5.31 mg.L-1. Various forms of coumaric acid widely existed in leaves.